Pemanfaatan Limbah Solid Pabrik Kelapa Sawit sebagai Media Tanam Alternatif pada Pembibitan Kelapa Sawit (Elaeis guineensis Jacq.) di Main Nursery - Febrianto, Eka Bobby; Tarigan, Sri Murti; Yosephine, Ingrid Ovie; Ardiansyah, Dede (JURNAL AGROPLASMA, 2024)
This research was conducted to determine the response of the growth of oil palm seedlings (Elaeis guineensis Jacq) with solid application as analternative planting medium in the main nursery. This research was conducted at the Agricultural High School Gardens and the Agricultural Agribusiness Laboratory (STIP-AP) Medan. This research was conducted from April to August 2019. This study used a non factorial randomized block design (RBD) with 4 replications, with a total sample of 48 samples. The parameters observed were plant height, stem diameter, leaf blade, number of roots, primary root length, root wet weight, crown wet weight, root dry weight and crown dry weight. The data obtained were statistically analyzed by analysis of variance (ANOVA). The results of this study indicate that the application of solid waste as analternative planting medium for oil palm nurseries (Elaeis guineensis Jacq) in the main nurseries has a significant effect on several parameters observed including stem diameter, number of leaves, and root dry weight. Keywords: decanter solid, seedlings, simalungun DxP varieties, palm oil, alternative